INNOVATION OF SEA FISH PUDDING AS A SOLUTION TO PREVENT STUNTING AND A NUTRITIOUS FOOD IN PANGGUNGREJO VILLAGE PASURUAN CITY - Eni Erwantiningsih; Richadatul Aisy; Erlina Eka Febrianti (Yayasan Education and Social Center, 2026)
This community service program was initiated in response to the limited variety and low nutritional quality of children’s snacks in the coastal area of Panggungrejo, Pasuruan. Many available snacks are inexpensive but lack essential nutrients needed for children’s growth and development. Therefore, this activity focuses on improving community awareness of nutrition by utilizing abundant local natural resources, especially sea fish, as the main ingredient for innovative food products. Sea fish was processed into fish pudding, a unique, nutritious, affordable, and child-friendly snack alternative. The implementation method included counseling sessions, interactive discussions, and hands-on assistance in product preparation. Participants were introduced to the nutritional benefits of fish and practical techniques for transforming it into attractive snacks with better market value. Through this program, the community is expected to gain new skills and knowledge in food processing, improve family nutrition, and develop creative business opportunities based on local marine resources, thereby supporting household income and coastal economic empowerment.